Small bowel entrapment and ureteropelvic junction disruption associated with L3 Chance fracture-dislocation - Pesenti, Sebastien (World J Clin Cases, 2016)
Paediatric Chance fracture are rare lesions but often associated with abdominal injuries. We herein present the case of a seven years old patient who sustained an entrapment of small bowel and an ureteropelvic disruption associated with a Chance fracture and spine dislocation following a traffic accident. Initial X-rays and computed tomographic (CT) scan showed a Chance fracture with dislocation of L3 vertebra, with an incarceration of a small bowel loop in the spinal canal and a complete section of the left lumbar ureter. Paraplegia was noticed on the initial neurological examination. A posterior L2-L4 osteosynthesis was performed firstly. In a second time she underwent a sus umbilical laparotomy to release the incarcerated jejunum loop in the spinal canal. An end-to-end anastomosis was performed on a JJ probe to suture the left injured ureter. One month after the traumatism, she started to complain of severe headaches related to a leakage of cerebrospinalis fluid. Three months after the traumatism there was a clear regression of the leakage. One year after the trauma, an anterior intervertebral fusion was done. At final follow-up, no neurologic recovery was noticed. In case of Chance fracture, all physicians should think about abdominal injuries even if the patient is asymptomatic. Initial abdominal CT scan and magnetic resonance imaging provide in such case crucial info for management of the spine and the associated lesions.